2018
DOI: 10.3390/f9050237
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Assessment of Crown Projection Area on Single Trees and Stand-Level, Based on Three-Dimensional Point Clouds Derived from Terrestrial Laser-Scanning

Abstract: Abstract:Crown projection area (CPA) is a critical parameter in assessing inter-tree competition and estimating biomass volume. A multi-layer seeded region growing-based approach to the fully automated assessment of CPA based on 3D-point-clouds derived from terrestrial laser scanning (TLS) is presented. Independently repeated manual CPA-measurements in a subset of the stand serve as the reference and enable quantification of the inter-observer bias. Allometric models are used to predict CPA for the whole stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…In recent years, terrestrial laser scanner (TLS) systems have been successfully applied in the context of forestry applications (e.g., [5,7,[10][11][12][13][14][15][16][17][18][19]). Using TLS, the structure of both vegetation and terrain can be automatically measured by means of massive clouds of XYZ points in 3D space [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, terrestrial laser scanner (TLS) systems have been successfully applied in the context of forestry applications (e.g., [5,7,[10][11][12][13][14][15][16][17][18][19]). Using TLS, the structure of both vegetation and terrain can be automatically measured by means of massive clouds of XYZ points in 3D space [5].…”
Section: Introductionmentioning
confidence: 99%
“…Because TLS technology is associated with novel standards and protocols, it is gradually influencing traditional methodology in the evaluation of forest structure attributes [10,21,22]. The main purpose of TLS-based research activities in the context of forest inventories is to enhance labor efficiency and replace manual measurements by automatic methods [5,7,16]. Early studies on the application of TLS in forest inventories revealed its high potential to derive precise measurements of single tree attributes (e.g., [5,[23][24][25][26]), but much effort is still required to analyze the TLS data.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with information obtained from the branching structure (Kankare et al 2013;Pyörälä et al 2018), the biomass estimates can be improved with observations derived directly from the point clouds (Yu et al 2013;Calders et al 2015;Stovall et al 2017). Detailed 3D reconstruction of trees and tree communities also enables the modelling of tree crown structure (Henning and Radtke 2006;Barbeito et al 2017;Trochta et al 2017;Ritter and Nothdurft 2018) to better understand phenomena such as the competition between trees (Metz et al 2013). Combining spectral information with geometric features expands the spectrum of observable phenomena, including such things as tree decline (Junttila 2019).…”
Section: Expanding the Spectrum Of Tree Observations Using Point Cloudsmentioning
confidence: 99%
“…Accurate representation of tree allometry (how the dimensions of a tree change with size), is therefore an important consideration for predictive modelling frameworks (Fischer et al., 2019). Theories about the morphology of crowns, such as metabolic scaling theory (MST, West et al., 2009), provide an attractive approach to generalising allometric scaling, but testing their accuracy is challenging with traditional ground measured data, which typically require assumptions of uniformity of crown morphology to estimate properties such as area and volume (Liang et al., 2016; Ritter & Nothdurft, 2018). Terrestrial laser scanning (TLS) offers a novel method of quantifying tree morphology in high‐resolution 3D detail (Disney, 2019), permitting testing of theoretical allometric relationships in detail never before possible.…”
Section: Introductionmentioning
confidence: 99%